Influence of germanium oxide on the mechanical properties of aluminum alloy - Sarvar Tursunbaev; Nodir Turakhodjayev; Shrofiddin Mardanokulov; Sherzod Tashbulatov (Genius Journals, 2023)
Currently, various studies are being conducted on alloying machine materials with various unique elements. In particular, studies were conducted to improve the properties of aluminum alloy by alloying elements such as lithium, zirconium, ytterbium, erbium into its composition. The wear resistance of the cast samples was determined using a device for measuring the wear resistance of a diamond stone.The research was tested in the laboratory of the department of Foundry Technologies of the Tashkent State Technical University.
Keywords: mechanical properties; germanium oxide; aluminum